Cities After Crisis Reinventing Neighborhood Design from the Ground-Up - Vazquez, Carlos Garcia (Taylor & Francis, 2022)
Cities After Crisis shows how urbanism and urban design is redefining cities after the global health, economic, and environmental crises of the past decades. The book details how these crises have led to a new urban vision-from avantgarde modern design to an artisan aesthetic that calls for simplicity and the everyday, from the sustainable development paradigm to a resilient vision that defends de-growth and the re-wilding of cities, from a homogenizing globalism to a new localism that values what is distinctive and nearby, from the privatization of the public realm to the commoning and self-governance of urban resources, and from top-down to bottom-up processes based on the engagement and empowerment of communities. Through examples from cities around the world and a detailed look at the London neighbourhood of Dalston, the book shows designers and planners how to incorporate residents into the decision-making process, design inclusive public spaces that can be permanently reconfigured, reimagine obsolete spaces to accommodate radically contemporary uses, and build gardens designed and maintained by the community, among other projects.